INTEGRASI NILAI-NILAI PENDIDIKAN ISLAM DALAM PEMBELAJARAN BAHASA INGGRIS - Nurul Ariza; Yuli Kuswandari; Sabarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The number of general subjects that have not been touched by religious values is the center of the researcher's attention. If you open the book of legislation, you will find the purpose of education to become a citizen who believes and is devoted to God Almighty. This paper aims to find out how the integration of Islamic education values in learning English which is a general subject. This research is a field research with qualitative method. Data collection is done through three ways, namely observation, documentation and interviews. The data analysis stage also uses three ways, namely the description or orientation stage, the reduction stage, and the selection stage. The respondents of this research are lecturers who teach English courses and fourth semester students in the Islamic Education Study Program (PAI) UIN Sunan Kalijaga Yogyakarta. The results showed that English learning which is a general course can be integrated in Islamic education values. This can be shown among others: Learning objectives of English courses have integration in Islamic values, the material given by lecturers to students is still related to Islamic education although not in a complex manner, the learning process always begins and ends with prayer, lecturers use active and cooperative learning methods to students, the learning process with discipline, the use of polite clothing during learning, and students have mutual respect when lecturers and friends speak.